Development and feasibility of the use of an assessment tool measuring treatment efficacy in patients with trimethylaminuria: A mixed methods study. Issue 2 (7th February 2019) - Rutkowski, Krzysztof; Rahman, Yusof; Halter, Mary
Abstract: Trimethylaminuria (TMAU) is a rare metabolic condition characterised by an unpleasant smell resembling rotting fish. Currently, the only measure of treatment efficacy is urine trimethylamine levels which do not always reflect the patient's experience of symptoms. A literature review did not find a specific tool to assess treatment efficacy from the patient's perspective. The aim of this study was to develop an assessment tool to provide a quantitative measure of treatment efficacy in patients diagnosed with TMAU before and after treatment and assess its acceptability (feasibility of use and face and content validity) to people living with TMAU. Mixed methods; a modified, four‐round Delphi by email and semi‐structured interviews conducted after clinical appointments. Delphi; Eight individuals living with TMAU from the TMAU forum, six medical consultants, and four dieticians in Metabolic Medicine in four National Health Service hospitals in England. Semi‐structured interviews; three patients with TMAU in two National Health Service hospitals, United Kingdom. The assessment tool contains 27 items distributed across four domains; Odour characteristics with 6 items, mental well‐being with 13 items, social well‐being with 5 items, and healthcare professionals support with 3 items. Semi‐structured interviews; views on the content and design of the tool. The co‐produced tool was successfully developed and considered acceptable to people living with TMAU. While further testing is needed to evaluate the validity and reliability of the assessment tool, the tool may serve as a prompt for questioning for clinicians diagnosing and treating TMAU.